2019
DOI: 10.2174/1566524019666190211120016
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mutations in Chinese Pathologic Myopic Patients and Contributions to Phenotype

Abstract: Purpose Pathologic myopia is a leading cause of visual impairment in East Asia. The aim of this study was to investigate the potential mutations in Chinese pathologic myopic patients and to analyze the correlations between genotype and clinical phenotype. Method One hundred and three patients with pathologic myopia and one hundred and nine unrelated healthy controls were recruited from Zhongshan Ophthalmic Center. Detailed clinical data, including ultra-widefield retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…observed the presence of a synonymous variant in this gene as pathological and the cause of EoHM presented by their patient. The authors suggested that although the variant does not alter the amino acid chain, the altered nucleotide can modify the secondary structure of the protein and can influence protein holding and gene expression [50]. PEX1 is a gene whose variants are related to defects in peroxisome biogenesis.…”
Section: Genes Related To Vitreoretinal Inherited Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…observed the presence of a synonymous variant in this gene as pathological and the cause of EoHM presented by their patient. The authors suggested that although the variant does not alter the amino acid chain, the altered nucleotide can modify the secondary structure of the protein and can influence protein holding and gene expression [50]. PEX1 is a gene whose variants are related to defects in peroxisome biogenesis.…”
Section: Genes Related To Vitreoretinal Inherited Diseasesmentioning
confidence: 99%
“…Variable expressivity and incomplete penetrance were found in this gene, which could be why the variant was also found in the father, who did not have a reported phenotype [66]. Chen S et al ( 2007) observed a family with ADOA, a novel OPA1 mutation, and a higher frequency of EoHM [50]. Nevertheless, the presence of EoHM in one family member without ADOA and OPA1 challenged the assumption that this mutation induced EoHM.…”
Section: Genes Related To Vitreoretinal Inherited Diseasesmentioning
confidence: 99%
“…In addition, as a key enzyme, retinol dehydrogenase 5 (RDH5) not only participates in the formation of 11-cis-retinol in the visual cycle, but also regulates the metabolism of RA/ATRA. Recent genetic studies have shown that RDH5 gene, mostly existed in retina, contributed to the pathogenesis of myopia [10][11][12].…”
Section: Introductionmentioning
confidence: 99%